Pengaruh Orientasi Kewirausahaan dan Inovasi Produk Terhadap Kinerja Usaha UMKM Kuliner di Kecamatan Singaparna Kabupaten Tasikmalaya - Ifqi Hasan Hudori Beq; Aditia Abdurachman (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2026)
This study examines how entrepreneurial orientation and product innovation contribute to the business performance of culinary micro, small, and medium enterprises (MSMEs) in Singaparna District, Tasikmalaya Regency. A quantitative approach with a survey design was employed. From a registered population of 200 active culinary MSME units, a total of 67 respondents were selected using the Slovin formula through simple random sampling. Data collection relied on a structured Likert-scale questionnaire with a response range of 1 to 5. The analytical pipeline involved ordinal-to-interval data transformation via the Method of Successive Intervals (MSI), followed by classical assumption diagnostics and multiple linear regression estimation. Empirical findings confirm that entrepreneurial orientation exerts a positive and statistically significant partial effect on business performance; product innovation likewise demonstrates a positive and significant partial influence. Taken in combination, the two independentt variables explain a substantial portion of the variance in business performance, with product innovation recording a higher regression coefficient and thus emerging as the stronger predictor. These findings carry strategic implications, underlining that sustained product innovation is a critical competitive lever for culinary MSMEs operating in semi-urban market settings.